2012
DOI: 10.1039/c2cp40781g
|View full text |Cite
|
Sign up to set email alerts
|

A crossed beam and ab initio investigation on the formation of vinyl boron monoxide (C2H3BO; X1A′) via reaction of boron monoxide (11BO; X2Σ+) with ethylene (C2H4; X1Ag)

Abstract: The reaction dynamics of the boron monoxide radical ((11)BO; X(2)Σ(+)) with ethylene (C(2)H(4); X(1)A(g)) were investigated at a nominal collision energy of 12.2 kJ mol(-1) employing the crossed molecular beam technique and supported by ab initio and statistical (RRKM) calculations. The reaction is governed by indirect scattering dynamics with the boron monoxide radical attacking the carbon-carbon double bond of the ethylene molecule without entrance barrier with the boron atom. This addition leads to a double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…60 Lastly, we observed that the CM angular distribution depicts a peak intensity at around y = 831 indicating that the decomposing complex preferentially emits a hydrogen atom almost parallel to the total angular momentum vector and nearly perpendicular to the rotational plane of the decomposing complex (sideways scattering). 58 These geometrical constraints have also been identified, for instance, in the reactions of isovalent cyano (CN) 61 and boron monoxide ( 11 BO) 26 radicals with ethylene.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…60 Lastly, we observed that the CM angular distribution depicts a peak intensity at around y = 831 indicating that the decomposing complex preferentially emits a hydrogen atom almost parallel to the total angular momentum vector and nearly perpendicular to the rotational plane of the decomposing complex (sideways scattering). 58 These geometrical constraints have also been identified, for instance, in the reactions of isovalent cyano (CN) 61 and boron monoxide ( 11 BO) 26 radicals with ethylene.…”
Section: Resultsmentioning
confidence: 96%
“…However, if we assume that the available energy is equilibrated among molecular degrees of freedom before the reaction occurs and considering that energy is conserved, the rate constants for the reaction steps can also be predicted by RRKM theory. 25,26 These calculations suggest that 92% of the vinylsulfidoboron molecule (C 2 H 3 BS) is formed via the unimolecular decomposition of i2, while only 8% of the final product is formed via the fragmentation of i1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we review the results of our crossed molecular beam experiments of four isovalent X 2 S + radicals -CN, 15,17,28 BO, 40,41 SiN, 37,38 and C 2 H 28,55,56 -with simple prototypical hydrocarbon reactants, acetylene (C 2 H 2 ) and ethylene (C 2 H 4 ). This approach will help us to elucidate generalized concepts on the chemical dynamics and the similarities and differences of the underlying mechanisms of the reactions of isovalent radicals with unsaturated hydrocarbons in extreme environments and their role in the formation of substituted hydrocarbons.…”
Section: Resultsmentioning
confidence: 99%
“…6,39 Finally, in rocket propulsion systems the combustion of boron offers three times the energy release than carbon, however boron readily forms oxides like boron monoxide that disrupt the combustion process by undergoing competing reactions with fuel components such as unsaturated hydrocarbons. [40][41][42][43] The multitude of simultaneous reactions in extreme environments makes for a difficult area of study. Only by systematically investigating the chemical dynamics of each contributing elementary reaction under single collision conditions will we be able to effectively model these complex environments.…”
Section: Introductionmentioning
confidence: 99%